Impacts of Climate Change on Georgia’s Coastal Zone : Vulnerability Assessment and Adaptation Options - World Bank (World Bank, Washington, DC, 2020)
The higher-level purpose of this study is to provide information to be used to raise the ambition of Georgia’s nationally determined contribution (NDCs) and to consider adaptation targets for the Black Sea coast of Georgia. The study also aims to highlight how supporting a blue economy can accelerate the implementation of adaptation measures required to reduce climate risks and contribute towards the region’s socioeconomic development and environmental conservation. The methodology used in the present study consists of five main steps: define the geographic scope; review available climate change projections; identify key climate risks and vulnerabilities for coastal Georgia; assess the impact of climate change on economic sectors and infrastructure, and possible adaptation options; and prioritize initial recommendations and key climate adaptation actions. The approach used to evaluate the various impacts on coastal Georgia consisted of a qualitative analysis and expert input from international and local teams. This included an assessment of feasible adaptation options. Discussions with local experts and government agencies were also carried out in order to gain further details of vulnerable areas and evaluate both the potential for specific adaptation measures to yield economic benefits as well as the feasibility and acceptability of these options. The report is organized in six chapters. Chapter one introduces the purpose, objectives, methodology, and limitations for the study. Chapter two provides an overview of Georgia’s coastal zone economic sectors, while chapter three provides an overview of Georgia’s coastal climate and climate change impacts. Chapter four presents the priority risks for coastal Georgia, based on the existing cost of environmental degradation estimates and climate change projections. Chapter five discusses the impacts of climate change on Georgian coastal economic sectors, health and infrastructure, through the prism of the priority risks described in the previous chapter and presents a menu of adaptation options. Chapter six discusses the conclusions of the study and makes initial information, institutional, and investment recommendations, and key actions, including key actions required to implement climate adaptation on the ground.